2020
DOI: 10.3390/coatings10100991
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Titanium Dioxide Coating by the Cold-Spray Process on Annealed Stainless Steel Substrate

Abstract: The surface of most metals is covered with thin native oxide films. It has generally been believed that to achieve bonding, the oxide covering the surface of metallic particles or metal substrates must be broken and removed by adiabatic shear instability (ASI), whether induced at the particle–substrate interface or at the particle–particle interface. The aim of the present research is to investigate the correlation between the remaining oxide amorphous layer and substrate-deformation with the adhesion strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…CS, due to its low process temperature, has been shown as an alternative process for producing photocatalytic nanostructured TiO 2 coatings (Ref 258 , 275 - 277 ). Research shows that spraying at lower temperatures prevents phase or surface morphology changes in the titanium dioxide, and therefore, the anatase and rutile phases of the feedstock powder can be retained in the TiO 2 coatings (Ref 258 , 259 , 277 , 278 ). However, being a ceramic material, deposition of TiO 2 powders using CS remains challenging as plastic deformation is typically required to promote substrate-particle and interparticle bonding.…”
Section: Cold Spray Application Pillars (Past Present and Future)mentioning
confidence: 99%
See 1 more Smart Citation
“…CS, due to its low process temperature, has been shown as an alternative process for producing photocatalytic nanostructured TiO 2 coatings (Ref 258 , 275 - 277 ). Research shows that spraying at lower temperatures prevents phase or surface morphology changes in the titanium dioxide, and therefore, the anatase and rutile phases of the feedstock powder can be retained in the TiO 2 coatings (Ref 258 , 259 , 277 , 278 ). However, being a ceramic material, deposition of TiO 2 powders using CS remains challenging as plastic deformation is typically required to promote substrate-particle and interparticle bonding.…”
Section: Cold Spray Application Pillars (Past Present and Future)mentioning
confidence: 99%
“…It is foreseen that during CS application the pure Ti core would deform while the TiO 2 shell may be shattered and trapped between Ti particles as well as on the surface. As CS typically maintains or even refines the powder’s crystalline structure (Ref 258 , 259 , 277 , 278 ), the TiO 2 nanostructures and heterogenous junctions grown on the Ti particles from the chemical treatments could potentially be maintained in the resulting Ti/TiO 2 coatings. Overall, CS applications of modified pure Ti having a TiO 2 oxide layer possess the potential of successful deposition that can be applied to various industries, particularly on-site coating deposition and repair in situations where components cannot or preferably not be dismantled.…”
Section: Cold Spray Application Pillars (Past Present and Future)mentioning
confidence: 99%
“…17,18 Immobilizing TiO 2 on supportive catalysts has been conducted in many studies and has shown promising findings. 19 Different coating methods can be used for coating the photoelectrodes by TiO 2 catalysts, including electrodeposition, 20 sol−gel, 21−24 sol−spray, 25 chemical vapor deposition, 26 thermal treatment, 27 and hydrothermal treatment. 28 The fabrication and morphologies of TiO 2 have been investigated in various studies through zero-dimensional (0D), one-dimensional (1D), two-dimensional (2D), and threedimensional (3D) nanostructures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Deposition and adhesion mechanisms [13,14] In the first topic, there were four publications related to the biomedical applications of ceramic coatings. Kyzioł et al [1] presented their work on the deposition of various multi-layer coatings based on diamond-like carbon structures deposited on low-density polyethylene (LDPE).…”
mentioning
confidence: 99%
“…The authors synthesized carbon-rich SiC coatings on Nextel fibers using the CVD method, proposed an empirical formula to calculate the coating thickness, and presented a detailed mechanism of the reactions taking place during the deposition of the coating on the surface of the fibers. The topic of coating-to-substrate adhesion was explored by Omar et al [14] in their work on the deposition of TiO 2 coating on stainless steel substrate by the cold-spray process. The obtained results proved the important role of annealing of austenitic 304 steel on the bonding of sprayed TiO 2 particles to its surface.…”
mentioning
confidence: 99%